2016
DOI: 10.1016/j.jcot.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Subungual osteochondroma: Nail sparing excision

Abstract: Subungual osteochondroma is a relatively uncommon benign bone tumor affecting mostly children and young adults, and is a major source of pain and nail deformity. Treatment consists of marginal excision and meticulous wound closure. In this report, we present three cases of subungual osteochondroma arising from the dorsal aspect of distal phalanx of the great toe, which were managed by marginal excision with preservation of nail apparatus under digital block anesthesia with the use of a ring tourniquet. We emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…There is a paucity of case reports on SO . Some previous reports suggested that cases diagnosed as SE were in fact SO .…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of case reports on SO . Some previous reports suggested that cases diagnosed as SE were in fact SO .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Another important condition in the differential diagnosis of SE is subungual osteochondroma (SO). 15,17,18 Histopathologically, SO features cortical and trabecular bone derived from endochondral ossification, with an overlying hyaline cartilage cap. 13,15 Tumors of incontinentia pigmenti Incontinentia pigmenti (IP) is a rare, X-linked dominant genodermatosis.…”
Section: Keratoacanthomamentioning
confidence: 99%
“…Although osteochondromas are the most common bone tumors, representing 10 to 15% of the totality, subungualosteochondromas is quite rare [1][2][3][4]. It is a benign osteocartilaginous tumor that usually involves the phalanges of the toes or fingers, affecting most commonly the distal phalanx of hallux [4].…”
Section: Dear Editormentioning
confidence: 99%
“…The first description is attributed to Dupuytren, in 1817. The author described as a bony outgrowth of the distal phalanx [3].…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation